Counsellors’ Perceived Causes and strategies for reducing suicidal thoughts among secondary school teenagers - Helen Efeyadu, Uzoekwe; Grace Chinyere, Nnadi; Obianuju Blessing, Mokwelu; Uju C, Nwanna; Taiwo Abiodun, Ojo (International Journal of Scientific Research and Management (IJSRM), 2023)
This study is carried out in Anambra state and it adopted the descriptive survey design. Two research questions guided the study. The sample size of the study comprised of 205 counsellors who are willing to participate in the study and they are drawn through accidental sampling techniques at their areas of meetings. The instrument used for data collection is the counsellors’ perceived causes and strategies for reducing suicidal thoughts among secondary school teenagers questionnaire (CSPCASFRSTASSTSQ). The reliability of the instrument coefficient value of 0.70 is established. On the spot administration is used in administering the instrument to ensure 100% return. The data collected in the study is analyzed using the arithmetic mean. The decision rule is that any of the response item for which the mean score is 2.5 and above is taken to mean that the factor exists while any response item for which the mean score is below 2.5 is taken as not being in existence. The study revealed that the causes of suicidal thoughts among other things include: lack of parental love and care, bullying among peers, substance over use, failures in examinations, sexual abuse and loneliness as the causes of suicidal thoughts among secondary school teenagers as perceived by the counsellors. The study also revealed that the counsellors’ perceived strategies for reducing suicidal thoughts among other things are : help them realize reasons to live and future goals, giving them academic support on how to succeed, teaching them the use of grounding techniques, learning the warning signs of suicidal thoughts as a starting point and offering guidance on ways to reach out to loved ones for support as strategies for reducing suicidal thoughts among secondary school teenagers. The researchers also recommended that government should ensure that every secondary school will have a professional counsellors handling secondary school students’ problems early enough before such escalates and also, school counsellors should be teaching parenting skills to improve family relationships for the betterment of all in the family during Parents’ Teachers Association meetings.